Analysis and Evaluation of the Influence of Different Drum Forms of Peanut Harvester on Pod-Pickup Quality - Bokai Wang; Fengwei Gu; Mingzhu Cao; Huanxiong Xie; Feng Wu; Baoliang Peng; Zhichao Hu (Agriculture, 2022)
Aiming at the problems of high missed-pickup rate and crushed rate caused by different types of peanut harvester pickup drums, by tracking a field comparative experiment from 2020 to 2021, the missed-pickup rate, missed-pickup quality distribution, crushed rate and quality distribution rule of pods with different degrees of crushing observed in two peanut varieties with different pickup drums were studied. Three kinds of pod-pickup drums were set up: axial flow (T1), tangential flow (T2) and tangential–axial flow (T3), and they were installed on the pickup harvester to form three kinds of pickup and harvest test stands. At the same time, a control test stand (CK) without pod-pickup drums was set up. Peanut varieties “Shanhua 9” and “Huayu22” and 10 water content levels were used. Using Origin2018 software, the missed-pickup rate, missed-pickup quality distribution, crushed rate and the quality distribution of pods with different degrees of crushing were statistically analyzed for the two peanut varieties harvested by different pickup drums. The results showed that the average missed-pickup rate was T1, T2 and T3, in order from small to large. The order of pickup quality from more to less was small pods, medium pods and large pods, which indicated that small pods were more likely to be missed. The average pod crushed rates for T1, T2 and T3 for Shanhua 9 were 2.06%, 2.19% and 2.45%, and those of T1, T2 and T3 for Huayu22 were 1.74%, 1.91% and 2.23%, so the order of pod crushed rates from small to large was T1, T2 and T3. At the same time, the crushed rate of T1, T2 and T3 to the two varieties decreased obviously with the decrease in water content. After the T1 test, the proportion of medium and severely crushed pods was the least, followed by T2, and the highest was T3. At the same time, the higher the water content, the higher the proportion of medium and severely crushed pods, and the proportion of medium and severely crushed pods after the Huayu22 test was less than that of the Shanhua 9 test.